Determining the Validity of the Professional Ethics Curriculum Model with a Mentoring Approach at Golestan University of Medical Sciences - Sofi , Marziyeh; Salimi, Ladan; Hoseini tabaghdehi , Leila (Assessment and Practice in Educational Sciences, 2026)
ABSTRACT The present study was conducted with the aim of determining the validity of the professional ethics curriculum model with a mentoring approach at Golestan University of Medical Sciences. The research was designed using a mixed-methods (qualitative and quantitative) approach. In the qualitative section, the grounded theory method was used to analyze in-depth interviews with experts and extract common themes. In the quantitative section, the current situation was investigated using a researcher-made questionnaire. The statistical population in the qualitative section consisted of 12 experts in the field of professional ethics and mentoring, who were selected using non-probability snowball sampling. In the quantitative section, 170 faculty members of Gorgan University of Medical Sciences were selected as the statistical sample. Data analysis was performed using MAXQDA, SPSS 21, and PLS 3.2 software. In the analysis of qualitative data, 128 indicators were identified across 9 dimensions and 25 components. The research results indicated that the professional ethics curriculum model with a mentoring approach possesses appropriate construct validity, and the data distribution was determined to be normal with a significance level of . The qualitative analysis led to the identification of 128 indicators in the form of 9 key dimensions, including education, skills, mentoring, technology, and accountability. Based on the index, the dimensions of “flexibility and motivation” and “technology and external content” had the highest predictive power with coefficients of and , respectively. Furthermore, the dimensions of “culture-building” with a coefficient of and “accountability” with a coefficient of demonstrated favorable performance in strengthening the connection between the university and society. In contrast, the “skills development” index with a coefficient of and “practical training” with a coefficient of recorded the lowest values, indicating the weaknesses of the model in transferring practical skills. This situation highlights the necessity of revising practical teaching methods and simulation workshops to bridge the gap between theory and practice. Overall, although this program has been successful in utilizing technology and fostering i ABSTRACT The present study was conducted with the aim of determining the validity of the professional ethics curriculum model with a mentoring approach at Golestan University of Medical Sciences. The research was designed using a mixed-methods (qualitative and quantitative) approach. In the qualitative section, the grounded theory method was used to analyze in-depth interviews with experts and extract common themes. In the quantitative section, the current situation was investigated using a researcher-made questionnaire. The statistical population in the qualitative section consisted of 12 experts in the field of professional ethics and mentoring, who were selected using non-probability snowball sampling. In the quantitative section, 170 faculty members of Gorgan University of Medical Sciences were selected as the statistical sample. Data analysis was performed using MAXQDA, SPSS 21, and PLS 3.2 software. In the analysis of qualitative data, 128 indicators were identified across 9 dimensions and 25 components. The research results indicated that the professional ethics curriculum model with a mentoring approach possesses appropriate construct validity, and the data distribution was determined to be normal with a significance level of . The qualitative analysis led to the identification of 128 indicators in the form of 9 key dimensions, including education, skills, mentoring, technology, and accountability. Based on the index, the dimensions of “flexibility and motivation” and “technology and external content” had the highest predictive power with coefficients of and , respectively. Furthermore, the dimensions of “culture-building” with a coefficient of and “accountability” with a coefficient of demonstrated favorable performance in strengthening the connection between the university and society. In contrast, the “skills development” index with a coefficient of and “practical training” with a coefficient of recorded the lowest values, indicating the weaknesses of the model in transferring practical skills. This situation highlights the necessity of revising practical teaching methods and simulation workshops to bridge the gap between theory and practice. Overall, although this program has been successful in utilizing technology and fostering interaction, training competent physicians requires fundamental reforms in the infrastructure of practical training and the enhancement of students’ ethical decision-making skills. The research results demonstrate that a professional ethics curriculum based on a mentoring approach is an efficient and effective strategy for training committed and ethically-oriented human resources in the healthcare system. Considering the positive role of this model in promoting a culture of interaction, motivating students, and utilizing modern technologies, it can be proposed as a superior model for other universities and medical education centers. nteraction, training competent physicians requires fundamental reforms in the infrastructure of practical training and the enhancement of students’ ethical decision-making skills. The research results demonstrate that a professional ethics curriculum based on a mentoring approach is an efficient and effective strategy for training committed and ethically-oriented human resources in the healthcare system. Considering the positive role of this model in promoting a culture of interaction, motivating students, and utilizing modern technologies, it can be proposed as a superior model for other universities and medical education centers.